'Now He Sings'. The My Musical Memories Reminiscence Programme: Personalised Interactive Reminiscence Sessions for People Living with Dementia. (April 2019) - Evans, Simon C; Garabedian, Claire; Bray, Jennifer
This paper explores the impact of the My Musical Memories Reminiscence Programme (MMMRP), an innovative intervention that adopts a music-based reminiscence approach. MMMRP builds on the format of the popular Singing for the Brain sessions with the aim of increasing opportunities for interaction and reminiscence amongst people living with dementia. Data were collected pre- and post-intervention and three months later using structured observation, interviews and focus groups. Results suggest that the programme had a positive impact on participants by promoting engagement, reminiscence and social interaction. For some individuals the impacts continued beyond their participation in the programme. A range of key facilitators for successful implementation of this approach were identified including the Session Leader role, the involvement of informal carers and the input of volunteers.